2018
DOI: 10.1186/s40659-018-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces cell cycle arrest and affects Trk receptor expression in human neuroblastoma SK-N-SH cells

Abstract: BackgroundArsenic trioxide (As2O3), a drug that has been used in China for approximately two thousand years, induces cell death in a variety of cancer cell types, including neuroblastoma (NB). The tyrosine kinase receptor (Trk) family comprises three members, namely TrkA, TrkB and TrkC. Various studies have confirmed that TrkA and TrkC expression is associated with a good prognosis in NB, while TrkB overexpression can lead to tumor cell growth and invasive metastasis. Previous studies have shown that As2O3 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The neuroblastoma cell line SK-N-BE (2) were cultured with gradient concentration of ATO for 24hours. Consistent with our previous research [24,25], the results revealed that ATO inhibited SK-N-BE(2) cells (Fig. 1).…”
Section: Ato Inhibit the Proliferation Of Sk-n-be (2) Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…The neuroblastoma cell line SK-N-BE (2) were cultured with gradient concentration of ATO for 24hours. Consistent with our previous research [24,25], the results revealed that ATO inhibited SK-N-BE(2) cells (Fig. 1).…”
Section: Ato Inhibit the Proliferation Of Sk-n-be (2) Cellssupporting
confidence: 92%
“…Our previous studies con rmed the anti-tumor growth effect of ATO in NB cells. ATO could inhibit the NB cells growth in vitro by means of arresting NB cells in G2/M phase [24], increasing TrkA/C receptors which related to the good prognosis of NB [25] and reducing multidrug-resistance protein [26]. Our previous work [27]found that ATO can restore the sensitivity of chemotherapy in some relapsed/refractory NB patients.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has investigated the effect and mechanism of the BDNF/TrkB/CREB signaling pathway in the cytotoxicity of BPS in SK-N-SH cells, which is a kind of human neuroblastoma cell and has been used in many previous studies of neurotoxicity. [21,22] This is one of the few studies in the literature exploring the neurotoxic mechanisms of BPS.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has investigated the effect and mechanism of the BDNF/TrkB/CREB signaling pathway in the cytotoxicity of BPS in SK-N-SH cells, which is a kind of human neuroblastoma cell and has been used in many previous studies of neurotoxicity. [21,22] These findings indicate that the apoptotic effect of BPS involved the mitochondria-mediated pathway of apoptosis, which involves an increase in the permeability of the mitochondrial membrane through damage to the membrane. Our results are similar to Qihua Pang's, which found that 100 μM BPS increase the ROS levels and apoptosis rates, and damage the cell membrane for HT-22 cells.…”
Section: Discussionmentioning
confidence: 99%
“…6 Our previous study along with others 1 demonstrated that treatment with ATO alone or combined with chemotherapeutic drugs exhibits a satisfactory cytotoxic effect on chemoresistant NB cells. TrkA, TrkB, and TrkC gene expression levels in an NB cell line are upregulated with increasing concentrations of ATO, 9 and treatment with ATO also reduces the expression of the resistance-associated protein, P-glycoprotein (P-gp). 7,8 We also found that preincubation with ATO followed by a mitosis-phase specific agent (vinorelbine or docetaxel) may have a higher anticancer ability compared with single drug treatment or followed by a non-mitosis-phase-specific agent (etoposide or cisplatin), 13 suggested that the combination strategy of ATO and different chemotherapeutics can lead to different tumor killing effects, and it might have clinical implications.…”
Section: Introductionmentioning
confidence: 99%